(untitled) (Revista "Boletín el Conuco", 2022)
The implementation of the Peace Agreement has brought with it a complex social and political scenario commonly known as the post-conflict, which poses great challenges for Colombian society. In this context, the academy plays a significant role at the territorial level as it articulates efforts aimed at guaranteeing the collective reparation of the victims of the armed conflict, as well as the defense of human rights. In this sense, the present work seeks to contribute to the strengthening of the Territory Observatory of the University of Los Llanos, by understanding the impact that falls on the commercial establishments of the municipality of Lejanías (Meta) between the years of 1997 and 2007. To Therefore, a mixed investigation was carried out with part of the commercial establishments located in said municipality. It is evident that during this period of time, some businesses suffered changes in their commercial activity, as well as in their net income and profit margin.